Growth and growth trajectory among infants in early life: Contributions of food insecurity and water insecurity in rural Zimbabwe - Koyratty, Nadia; Ntozini, Robert; Mbuya, Mduduzi; Jones, Andrew D.; Schuster, Roseanne C.; Kordas, Katarzyna; Li, Chin-Shang; Tavengwa, Naume V.; Majo, Florence D.; Humphrey, Jean; Smith, Laura E. (BMJ, 2022)
Introduction Stunting or linear growth faltering, measured by length-for-age Z-score (LAZ), remains a significant public health challenge, particularly in rural low-income and middle-income countries. It is a marker of inadequate environments in which infants are born and raised. However, the contributions of household resource insecurities, such as food and water, to growth and growth trajectory are understudied. Methods We used the cluster-randomised Sanitation Hygiene and Infant Nutrition Efficacy trial to determine the association of household-level food insecurity (FI) and water insecurity (WI) on LAZ and LAZ trajectory among infants during early life. Dimensions of FI (poor access, household shocks, low availability and quality) and WI (poor access, poor quality, low reliability) were assessed with the multidimensional household food insecurity and the multidimensional household water insecurity measures. Infant length was converted to LAZ based on the 2006 WHO Child Growth Standards. We report the FI and WI fixed effects from multivariable growth curve models with repeated measures of LAZ at 1, 3, 6, 12 and 18 months (M1–M18). Results A total of 714 and 710 infants were included in our analyses of LAZ from M1 to M18 and M6 to M18, respectively. Mean LAZ values at each time indicated worsening linear growth. From M1 to M18, low food availability and quality was associated with lower LAZ (β=−0.09; 95% −0.19 to –0.13). From M6 to M18, poor food access was associated with lower LAZ (β=−0.11; 95% −0.20 to –0.03). None of the WI dimensions were associated with LAZ, nor with LAZ trajectory over time. Conclusion FI, but not WI, was associated with poor linear growth among rural Zimbabwean infants. Specifically, low food availability and quality and poor food access was associated with lower LAZ. There is no evidence of an effect of FI or WI on LAZ trajectory.